Desain taman sensori bagi anak berkebutuhan khusus tunanetra tingkat sekolah dasar studi kasus Sekolah Luar Biasa (SLB) Negeri 1 Denpasar - Roxane Dewi Ria Hidayat; Anak Agung Keswari Krisnandika; I Made Agus Dharmadiatmika (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Sensory garden is a garden that function to strengthen the ability of five human senses. Therefore, the locating selection of sensory garden should be appropriate in order that the purpose of giving educational facilities and sensory therapy for children with special needs can be carried out optimally. Special Needs School (SLB) is considered appropriate because sensory therapy is one of alternatives to strengthen children with special needs ability. SLB Negeri 1 Denpasar is one of the public special needs schools located in Denpasar, specifically at Jalan Serma Gede. SLB Negeri 1 Denpasar is being chose because it has a strategic location, which is belong to one of education zones in Denpasar and has an open space therefore it can be used as a therapy zone for school students. The data was collected by survey method. data collection technique through (atau including) interview, observation, and literature studies were done to obtain primary and secondary data. The result of this study is a design with the concept of therapy and education that were safe and secure for blind children.